Chemical Oxidation Applications for Industrial Wastewaters - Tunay, Olcay (IWA Publishing, 2010)
This book covers the most recent scientific and technological developments in the field of chemical oxidation processes applicable for the efficient treatment of biologically-difficult-to-degrade, toxic and/or recalcitrant effluents originating from different manufacturing processes. It is a comprehensive review of process and pollution profiles as well as conventional, advanced and emerging treatment processes & technologies developed for the most relevant and pollution (wet processing)-intensive industrial sectors. It addresses chemical/photochemical oxidative treatment processes, case-specific treatability problems of major industrial sectors, emerging (novel) as well as pilot/full-scale applications, process integration, treatment system design & sizing criteria (figure-of-merits), cost evaluation and success stories in the application of chemical oxidative treatment processes.